Effects of the move towards renewables on the power system reliability and flexibility in South Korea - Daiki Min; Jong-hyun Ryu; Dong Gu Choi (Energy Reports, 2020)
The plan to shift towards renewable energy has recently become the central part of the energy policy on the power system in South Korea. The sudden shift towards renewable energy has raised questions regarding the reliability and flexibility of the power system. This paper proposes a research framework to evaluate the new policy in South Korea from various aspects using three simulation models in a series. The first optimal generation model finds the optimal electricity generation mix and provides the total generation cost and environmental impact of the given long-term capacity expansion plan. The other two simulation models assess the reliability and flexibility of power systems, respectively. Within the research framework, we introduce a new probabilistic index to quantitatively measure the flexibility. The results of applying the framework into the new policy show that the policy fails to guarantee the target reliability level and increases costs and emissions. Achieving target system reliability will require additional capacity, and system flexibility is very sensitive to the type of capacity added. If the Korean government decides to add more capacity, natural gas turbine power plants turn out to be a good option from the point of economic, environmental, and flexibility considerations.
Keywords: 330; Policy evaluation; Power system planning; Simulation models; System flexibility; System reliability